2020
DOI: 10.4103/jcas.jcas_184_19
|View full text |Cite
|
Sign up to set email alerts
|

Full-thickness skin graft fixation techniques: A review of the literature

Abstract: Multiple techniques for skin graft fixation have been proposed, but the evidence underlying these techniques is unclear. This study aimed to review the literature for full-thickness graft fixation techniques. PubMed was electronically searched to identify relevant studies. The search strategy identified 91 relevant articles. These consisted of 2 randomised controlled trials (RCTs), 10 observational cohort studies (8 retrospective, 2 prospective), and 79 descriptive studies (case series, case reports, or expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Postoperative fixation is important for successful survival of skin grafts with various methods such as tie-overs with cotton balls and gauze often used. 1 Originally intended for wound healing, the fixation of skin grafts by NPWT was first reported by Schneider et al. in 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative fixation is important for successful survival of skin grafts with various methods such as tie-overs with cotton balls and gauze often used. 1 Originally intended for wound healing, the fixation of skin grafts by NPWT was first reported by Schneider et al. in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Skin grafting contaminated wounds caries a risk of wound infection and graft loss during the fixation period which typically ranges from 3 to 10 days. 1 Negative Pressure Wound Therapy (NPWT) has become a major alternative method for graft fixation, however regular NPWT is contraindicated for contaminated and infected wounds. 2 , 3 To overcome this challenge, we report the use of NPWT with Instillation and Dwelling (NPWTi-d) for skin graft fixation and dressing in contaminated complex wounds.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multiple methods have been described including basting or quilting sutures, tie-over and non-tie over boluses, sponge bolster, negative pressure dressings and cyanoacrylate adhesive. 3,6,7 Several studies have shown that traditional tie-over boluses are not essential, as other fixation techniques have been shown to have comparable results in terms of graft survival, aesthetics and complication rates. 6,7 Traditionally, bolus dressings are removed after 5-7 days.…”
Section: Skin Grafts: a Survey Study Of Australasian Mohs Surgeonsmentioning
confidence: 99%
“…3,6,7 Several studies have shown that traditional tie-over boluses are not essential, as other fixation techniques have been shown to have comparable results in terms of graft survival, aesthetics and complication rates. 6,7 Traditionally, bolus dressings are removed after 5-7 days. This was reflected in the results of our survey with the majority removed at 1 week.…”
Section: Skin Grafts: a Survey Study Of Australasian Mohs Surgeonsmentioning
confidence: 99%
“…Mechanism of action of this highly effective method remains not completely understood. 1 Skin graft fixation 2 and muscle flap edema reduction 3 by means of NPWT suggest that its beneficial effects are rather due to compression than due to depressurization. The initial belief that NPWT diminishes tissue pressure and improves blood circulation has appeared inconsistent with experimental findings which show an increase in the pressure 4-6 and reduction in perfusion.…”
mentioning
confidence: 99%